Present century snow core record of organolead pollution in Greenland - Lobinski, Ryszard; Boutron, C.F.; Candelone, J.-P.; Hong, S.; Szpunar-Lobinska, J.; Adams, F.C. (HAL CCSD, 1994)
International audience Ionic alkyllead species have been determined in precisely dated consecutive layers of a 25-m-deep snow core obtained by drilling at the Summit site, relying on ultraclean sampling, high-resolution separation of individual species, and ultrasensitive determination procedures. Ethylleads were the only species found in the concentration ratio varying from 5 to 400 fg/g. The concentrations found show an increasing trend since the early 1970s until the late 1980s that is slightly blurred by seasonal variations. The results are correlated with the data on the distribution of organolead species in gasoline, the consumption levels of leaded gasoline in Europe and the United States, and the concentrations and isotopic compositions of total lead in particular samples. Unambiguous evidence of the gasoline-related sources of lead in aged Greenland snow and ice during the past 70 years are provided. In contrast to Pb-(II), no dramatic drop in the northern hemispheric pollution by organic lead in the 1970s is observed. © 1994 American Chemical Society.